Implementation of a Development Program for Elderly Convicts at the Class I Penitentiary in Medan - Arifin Alexander; Kartina Pakpahan; Elvira Fitriyani Pakpahan (Faculty of Law, Merdeka University Surabaya, Indonesia, 2024)
The aim of this research is to analyze and understand the implementation of guidance for elderly prisoners at the Medan Class I Penitentiary. This research method uses a juridical-empirical research method, the data obtained from this research is processed and analyzed quantitatively descriptively. Where all data obtained is analyzed in its entirety to give rise to a systematic and factual picture. After analysis, the author draws conclusions which will ultimately result in preventive and normative actions regarding the problems that have been raised. The results of the coaching research carried out by the Medan Class I Correctional Institution are in accordance with Law Number 22 of 2022 concerning Corrections. As well as the implementation of coaching for inmates based on Government Regulation 31 of 1999 concerning the Guidance and Guidance of Correctional Inmates, where the aim of coaching is to shape corrections inmates to become human beings who realize their mistakes, improve themselves, and not repeat criminal acts again, so that they can be accepted again. in the community environment and in the final stage entering the integration process carried out by the Correctional Center (Bapas). Personality and independence development has been implemented for all elderly correctional residents in accordance with the rights that must be fulfilled. In undergoing guidance, elderly prisoners also obtain their rights based on Law number 13 of 1998 concerning the welfare of the elderly. This is proven by the presence of one of the elderly residents who received training and the opportunity to work in the field of work activities, especially sewing activities.